1995
DOI: 10.1152/ajpregu.1995.268.2.r549
|View full text |Cite
|
Sign up to set email alerts
|

Rates of local cerebral protein synthesis in the rat during normal postnatal development

Abstract: The degree of recycling of leucine derived from protein breakdown into the precursor pool for protein synthesis was measured in rat brain at different postnatal ages, and age-specific values were used in the calculation of regional (local) rates of cerebral leucine incorporation into protein (lCPSleu) in 44 brain regions and the brain as a whole. Early in development, a greater fraction of the precursor leucine pool is derived from protein breakdown, indicating that protein degradation is higher in young rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…Mean arterial blood pressure, hematocrit, and arterial plasma glucose concentrations were measured to evaluate each animal's physiological state, as previously described (22). Body temperature was monitored with a Model BAT-12 thermometer (Sensortek, Clifton, NJ) or a microprobe implanted in the peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean arterial blood pressure, hematocrit, and arterial plasma glucose concentrations were measured to evaluate each animal's physiological state, as previously described (22). Body temperature was monitored with a Model BAT-12 thermometer (Sensortek, Clifton, NJ) or a microprobe implanted in the peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%
“…injection of sodium pentobarbital, and brains were rapidly removed and frozen in isopentane cooled to Ϫ40°C with dry ice. Serial sections, 20 m thick, were cut in a Leica 3050 cryostat (Leica, Deerfield, IL) at Ϫ18°C, thaw mounted on gelatin-coated slides, air dried, fixed, and washed in 10% formalin, and exposed to EMC-1 film (Kodak) along with calibrated [ 14 C]methylmethacrylate standards as previously described (22). Autoradiograms were analyzed with an AIS image processing system (Imaging Research, St. Catherine's, ON, Canada) with a pixel size of 28 m. The concentration of 14 C in each region of interest was determined from the optical density vs. 14 C concentration curve determined from the calibrated plastic standards, and lCPS leu was calculated by means of Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study in fetal sheep by Abrams and colleagues (1) using [ 14 C]leucine autoradiography reported a rate of leucine incorporation into brain protein of ϳ5 nmol ⅐ g Ϫ1 ⅐ min Ϫ1 , with an overall increase through the latter part of gestation and into the early postnatal period likely reflecting cerebral myelination. Postnatal studies in rats have similarly shown high rates of brain protein synthesis during early development, with peak values occurring shortly after birth and gradually decreasing thereafter (6,26). While high rates of cerebral protein synthesis are thus evident during early life in both sheep and rats in support of the brain's growth and development, these rates are considerably greater than anticipated protein accretion, indicating that protein degradation must also play an active role in the development of the brain (6).…”
mentioning
confidence: 99%
“…brain protein directly related to maturational events (26). Initial study in the near-term ovine fetus by Schaefer and Krishnamurti (24) using a tyrosine isotopic-dilution technique showed high rates of cerebral protein synthesis with a fractional protein synthetic rate between 14 and 37%/day and an absolute rate of synthesis of ϳ1 g/day.…”
mentioning
confidence: 99%